Intermittent Dobutamine Therapy Reduced Hospitalization and Improve Mortality in Chronic Heart Failure Patient - Saha, Ranajit; Rahman, Majibar; Islam, Mahfuzul; Ali, Younus; Hasan, Rakibul; Alam, Mashkurul (Cardiology and Cardiovascular Medicine, 2025)
Background: Chronic heart failure (CHF) remains a significant health burden despite advances in therapy. This study aimed to evaluate the efficacy and safety of intermittent dobutamine therapy (IDT) in reducing hospitalizations and improving mortality in CHF patients. Methods: In this prospective, single-center study, 100 patients with CHF (LVEF ≤35%, NYHA class III-IV) were randomized to receive either IDT plus standard care or standard care alone. The IDT group received monthly 6-hour dobutamine infusions monthly (5 μg/kg/min) for 3 months and the dosage has been gradually reduced and discontinued. The primary outcome was a composite of all-cause mortality and heart failurerelated hospitalizations at 12 months. Secondary outcomes included changes in left ventricular ejection fraction (LVEF),N-terminal pro-Btypenatriureticpeptide( NT-proBNP) levels, 6-minute walk test (6MWT) distance, and quality of life scores. Results: The primary composite outcome occurred in 18 patients (36%) in the IDT group compared to 29 patients (58%) in the standard care group (hazard ratio 0.53; 95% CI 0.29- 0.95; p=0.03).At 12weeks, the IDT group showed greater improvements in LVEF (+5.8%vs+1.2%, p<0.001), NTproBNP levels (median change: -980 pg/mLvs -210 pg/mL, p=0.002), 6MWT distance (+48 m vs +12 m, p<0.001), and quality of life scores (-18 points vs -5 points, p<0.001). The incidence of adverse events was similar between groups. Conclusions: Intermittent dobutamine therapy significantly reduced the composite of mortality and heartfailure-related hospitalizations in CHF patients,while improving cardiac function,functional capacity, and quality of life. These findings suggest that IDT may be a promising therapeutic strategy for selected patients with advanced heart failure.